Incidental extra cystic findings in autosomal dominant polycystic kidney disease: beyond the liver and kidney - Srinivas, Rohith; N., Gurukanth Rao; G., Balachandra (International Journal of Advances in Medicine, 2025)
Autosomal dominant polycystic kidney disease (ADPKD) is a genetic disorder primarily affecting the kidneys and liver, but its systemic nature can lead to unexpected extrarenal findings. This report describes a 55-year-old woman with ADPKD who presented with hypertension and abdominal discomfort. Diagnostic imaging uncovered not only typical renal and hepatic cysts but also rare incidental lesions-a caecal lipoma, ovarian dermoid, and diverticulum. Surprisingly, she later developed synchronous bilateral breast cancer, suggesting a possible link between ADPKD and malignancy. These findings highlight the need for comprehensive evaluation in ADPKD patients, as extrarenal manifestations may signal underlying comorbidities. A multidisciplinary approach is essential for early detection and management of such complex presentations, emphasizing the importance of regular surveillance beyond renal and hepatic involvement.